Atomic-Scale Interface Modification in Complex Oxide Heterojunctions for Near-Infrared Photodetection - Ryou, Sanghyeok; Mo, Sanghyeon; Kim, Doyeop; Choi, Sungjun; Oh, Jaewhan; Yang, Yongsoo; Eom, Kitae; Lee, Hyungwoo (ACS Nano, 2024)
Photodetectors that detect near-infrared (NIR) light serve as important components in contemporary energy-efficient optoelectronic devices. However, detecting the low-energy photons of the NIR light has long been challenging since the ease of photoexcitation inevitably involves increasing the background current in the dark. Herein, we report the atomic-scale interface modification in SrRuO3/LaAlO3/Nb-doped SrTiO3 (SRO/LAO/Nb:STO) heterostructures for NIR photodetection. The interfacial band alignment by a polar monolayer LAO allows precise tuning of the Schottky barrier to achieve a specific energy band profile suitable for the NIR photodetection. The SRO/LAO/Nb:STO heterojunctions show a high photoresponsivity up to ∼1.1 mA/W under NIR light irradiation (λ = 850 nm), while keeping the pA-scale dark current. The increase in the responsivity by interface modification is evaluated at a maximum of 1371%. Based on the enhanced NIR photoresponsivity, as a proof of concept, we demonstrate the spatial imaging of NIR signals using a conceptual array of SRO/LAO/Nb:STO heterojunctions. In addition, the experimental-data-based simulation verifies that the array device can implement pulse-number-dependent plasticity, which is based on the characteristic persistent photoconductivity. This study suggests that atomic-scale interface modification is a facile and powerful method for optimizing the photoresponsive properties of complex-oxide-based heterojunctions.
Keywords: Band alignments; Interfacial band alignment; LaAlO 3; Near Infrared; Near-infrared; Near-infrared photodetection; Perovskite oxides; Photo detection; Polar layers; Schottky junctions; interfacial band alignments; LaAlO3; near-infrared photodetection; perovskite oxide; polar layer; Schottky junctions